ADEGAN KEKERASAN DALAM TAYANGAN HIBURAN DI TELEVISI (STUDI KASUS TAYANGAN YUK KEEP SMILE DI TRANS TV) - Valentina, Leena Miller (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2017)
This research studying about violence in entertainment shows on television, impressions studied were Yuk Keep Smile ( YKS ). This study used a qualitative method of discourse analysis approach. Data collection techniques consist of literature, look and listen, sorting and grouping, and documentation. The results showed that YKS are impressions that only focuses on the elements of entertainment without balanced with educational elements in it. In the impressions YKS also contains elements of violence, including in the form of physical violence, psychological violence and symbolic violence. In every scene that is considered funny by the audience actually contains many scenes of violence. In one scene, can contain many forms of violence at once or can be called complex violence, that in one scene there are forms of physical, psychological, and symbolic. YKS audience response to the show through various media, social media, media and direct action that there are people who respond oppose, because they are not educated and those that support because they have a concept of creative and entertaining.Keywords: Violence, Impressions Entertainment, Yuk Keep Smile